2019
DOI: 10.1167/19.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spatial attention on spatiotopic visual motion perception

Abstract: #We almost never experience visual instability, despite retinal image instability induced by eye movements. How the stability of visual perception is maintained through spatiotopic representation remains a matter of debate. The discrepancies observed in the findings of existing neuroscience studies regarding spatiotopic representation partly originate from differences in regard to how attention is deployed to stimuli. In this study, we psychophysically examined whether spatial attention is needed to perceive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…Previous work suggests that world-centered aftereffects can be fragile, for phenomena such as duration compression ( Bruno, Ayhan, & Johnston, 2010 ; Burr, Tozzi, & Morrone, 2007 ), motion ( Knapen, Rolfs, & Cavanagh, 2009 ; Turi & Burr, 2012 ), and tilt aftereffects ( Knapen, Rolfs, Wexler, & Cavanagh, 2010 ; Melcher, 2005 ), although reasons for these inconsistent findings in previous work and this work are not clear. Lack of evidence for an aftereffect in the world-centered reference frame in Experiment 5 is in general agreement with previous work showing that attentional and memory factors can affect the remapping of information about objects in the visual field to world-centered coordinates ( Crespi et al, 2011 ; Laurin et al, 2021 ; Mathot & Theeuwes, 2011 ; Prime, Vesia, & Crawford, 2011 ; Yao, Treue, & Krishna, 2016 ; Yoshimoto & Takeuchi, 2019 ). In Experiment 5 , in comparison to the earlier experiments, there were multiple positions on the screen where stimuli were presented across blocks.…”
Section: Discussionsupporting
confidence: 91%
“…Previous work suggests that world-centered aftereffects can be fragile, for phenomena such as duration compression ( Bruno, Ayhan, & Johnston, 2010 ; Burr, Tozzi, & Morrone, 2007 ), motion ( Knapen, Rolfs, & Cavanagh, 2009 ; Turi & Burr, 2012 ), and tilt aftereffects ( Knapen, Rolfs, Wexler, & Cavanagh, 2010 ; Melcher, 2005 ), although reasons for these inconsistent findings in previous work and this work are not clear. Lack of evidence for an aftereffect in the world-centered reference frame in Experiment 5 is in general agreement with previous work showing that attentional and memory factors can affect the remapping of information about objects in the visual field to world-centered coordinates ( Crespi et al, 2011 ; Laurin et al, 2021 ; Mathot & Theeuwes, 2011 ; Prime, Vesia, & Crawford, 2011 ; Yao, Treue, & Krishna, 2016 ; Yoshimoto & Takeuchi, 2019 ). In Experiment 5 , in comparison to the earlier experiments, there were multiple positions on the screen where stimuli were presented across blocks.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Yoshimoto et al (2014) showed that positive priming was predominantly reported in spatiotopic coordinates, implicating the role of frontal-parietal regions ( Liu, Yu, Peter, & Cavanagh, 2019 ). In a later study Yoshimoto and Takeuchi (2019) found that directing attention away from the ambiguous test stimulus abolished the positive priming effect, strongly suggesting that attention is needed to induce positive priming. Recently, we showed that modulating participant's expectations about the range of possible motion sequences they might perceive influenced their reports of positive priming but failed to affect reports of negative priming ( Heller & Davidenko, 2018 ).…”
Section: Introductionmentioning
confidence: 94%
“…There is evidence that the different percepts determined by stimulus parameters result from separate underlying mechanisms, one producing negative priming and the other producing positive priming ( Pantle, Gallogly, & Piehler, 2000 ; Kanai & Verstraten, 2005 ; Yoshimoto et al, 2014 ; Heller & Davidenko, 2018 ; Yoshimoto & Takeuchi, 2019 ). Moreover, the evidence suggests that positive priming involves processes that are higher order than those responsible for negative priming.…”
Section: Introductionmentioning
confidence: 99%